Questions of context reading a century of German mission theology - Flett, John G. 1972-; Wrogemann, Henning 1964- (Missiological engagements, 2020)
The gospel is for every tribe, tongue, and nation (Revelation 7:9), but there is no single biblical or theological model for the relationship between the gospel and these diverse cultures. Indeed, every suggested approach carries its own range of philosophical and theological commitments that all too often remain unexamined. Contextualization is fraught with challenges—yet wrestling with questions of context is essential for how we understand mission, theology, and the embodiment of the Christian faith. German missiology has engaged these questions in a variety of ways that can both inform and critique Anglo-American traditions. In this compilation and analysis, John Flett and Henning Wrogemann translate and comment on a core thread of German missiological works, explaining both their historical and current significance. Drawn from journals and books across a century of academic discourse, these classic writings trace developments from Gustav Warneck, the father of contemporary missiology, through key thinkers such as Karl Hartenstein, who coined the term missio Dei, down to twenty-first century discussions of intercultural hermeneutics. Along the way they reveal advances, mistakes, and changing definitions as German missiologists interacted with the cultural and political realities of their time. This longitudinal study, showcasing many texts available in English for the first time, tackles the history and dynamics of contextualization head-on and sheds new light on the state of missiology today. We are reminded, Flett and Wrogemann argue, that we must keep working to honor difference within the worldwide Christian community as necessary to the fullness of our being in Christ. --